When Public Health Becomes Politicized. Issue 5 (September 2017) - Lerner, Barron H.
Abstract: Perhaps nothing symbolizes the current polarized political climate in the United States more than the world of public health. Public health schools and health departments are full of "true believers, " people willing to crusade for any program designed to reduce morbidity and mortality. But in the "real world, " proven programs and strategies—such as gun‐control measures, universal vaccination, and improved traffic safety—are routinely thwarted. Why do critics oppose efforts to improve the public's health? History can provide some answers.